ELECTROCHEMICAL SENSOR TO MONITOR LEAD IN NATURAL WATER FOR PUBLIC SUPPLY - Abrão, Ana Letícia Santos; de Faria, Jenniffer Cecília Noronha; Malpass, Geoffroy Roger Pointer; da Luz, Mário Sérgio; Ferreira, Deusmaque Carneiro (Seven Editora, 2025)
Potentially toxic metals are capable of bio-accumulating in body tissues of living organisms and of having toxicological effects on both soil properties and the health of humans and animals. There are several methodologies available to quantify metals in aqueous matrices, however, these techniques are expensive, given their high cost and need of experts to manage the equipment. Accordingly, the present study introduces the application of an Au electrode, without surface modification, to analyze the presence of Pb2+ ions in surface water collected from Lanoso Brook, Uberaba City - MG, Brazil. The technique of anodic stripping voltammetry, without the need of sample preparation was employed. Volumetric parameters were optimized with the aid of central composite rotational design (CCRD) and method validation was carried out in atomic emission spectrophotometer. A detection limit (DL) of 0.04 ng L-1 and quantification limit (QL) of 0.13 ng L-1 were determined. Moreover, Pb2+ was found in real samples, and this finding highlighted the effectiveness of employing the Au electrode in this role. DOI: https://doi.org/10.56238/sevened2025.036-031